Pengaruh Penggunaan Instagram Terhadap Karakter Peserta Didik di Kelas X SMA Negeri 3 Parepare - Salmiati, Salmiati; Ningsi, Yustia; Ramlah, Ramlah (JPPI (Jurnal Pendidikan Islam Pendekatan Interdisipliner), 2019)
The research consists of three research problems; (1) in what way is Instagram used, (2) what is the character of students, and (3) is there significant effect of Instagram toward the students’ character in class X at SMA Negeri 3 Parepare. The research applied survey research. The technique of data collection used questionnaire, interview, and observation. The population of the research involved as many as 46 class X students. The result of the research revealed (1) that the intensity of the use of Instagram by the students of class X of SMA Negeri 3 Parepare was in high category. It was shown by the questionnaire result which was 45, 2%. The value was in the interval between 26% - 50% which was high, (2) The character of the class X students of SMA Negeri 3 Parepare was in good category. It was shown by the questionnaire result which was 49, 8 %. The value was in the interval between 26% - 50% which was good, (3) The effect of Instagram toward the character of class X students of SMA Negeri 3 Parepare can be concluded having positive effect based on the calculation using product moment and interview technique. As general reveal of the research, the intensity of the use of Instagram has positive effect toward the character of class X students of SMA Negeri 3 Parepare